Peculiarities of Modelling of Vapour-Liquid Flows of Bubble Structure - Pavlenko Anatoliy (Environmental and Climate Technologies)
This review comprehensively analyses the modelling methodologies employed for vapour-liquid flows exhibiting bubble structures, phenomena frequently observed in a multitude of engineering applications operating under metastable thermodynamic conditions. These flows play a crucial role in intensifying various technological processes, with examples including explosive boiling in steam generators, boilers, and high-temperature gas reactors. This manuscript critically evaluates existing modelling approaches and proposes innovative strategies to enhance the accuracy and predictive capability of mathematical models for these complex phenomena, focusing on the challenges posed by non-equilibrium effects and the need for improved closure relationships.